2016
DOI: 10.1039/c6cp05035b
|View full text |Cite
|
Sign up to set email alerts
|

Probing the microhydration of metal carbonyls: a photoelectron velocity-map imaging spectroscopic and theoretical study of Ni(CO)3(H2O)n

Abstract: Abstract:A series of microhydrated nickel carbonyls, Ni(CO) 3 (H 2 O) n -(n = 0-4), are prepared via a laser vaporization supersonic cluster source in the gas phase and identified by mass-selected photoelectron velocity-map imaging spectroscopy and quantum chemical calculations. Vertical detachment energies for the n = 1-4 anions are measured from the photoelectron spectra to be 1.429 ± 0.103, 1.698 ± 0.090, 1.887 ± 0.080, and 2.023 ± 0.074 eV, respectively. The C-O stretching vibrational frequencies in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The frequency observed for the Ni-CO species is in the same range as the stretching frequency observed for Ni(CO) 4 (2056 cm −1 ), suggesting the formation of a Ni 0 -CO species. 33,34 However, based on these experiments no statement about the exact nature of the reduced species can be made. Furthermore, this band is not observed when the experiments were performed in pure acetonitrile (non-catalytic conditions) or pure water (only H 2 formation).…”
Section: Electrocatalytic Co 2 Reductionmentioning
confidence: 99%
“…The frequency observed for the Ni-CO species is in the same range as the stretching frequency observed for Ni(CO) 4 (2056 cm −1 ), suggesting the formation of a Ni 0 -CO species. 33,34 However, based on these experiments no statement about the exact nature of the reduced species can be made. Furthermore, this band is not observed when the experiments were performed in pure acetonitrile (non-catalytic conditions) or pure water (only H 2 formation).…”
Section: Electrocatalytic Co 2 Reductionmentioning
confidence: 99%
“…Previous studies have shown that the polarity and number of solvent molecules have significant effects on the charge transfer and solvation structure between solute anions and solvent molecules. Plenty of studies have shown that there are mainly two kinds of interactions: nonconventional hydrogen bonds (NHBs) and conventional hydrogen bonds (HBs) between the solute metal anions and solvent water molecules using infrared photodetachment spectrum and photoelectron spectroscopy method. These two kinds of interaction compete with each other, and the dominant interaction changes in different solvent environments. However, the interaction between other solvent molecules and metal anions is rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…It had a two-dimensional imaging detector, and the density of the photoelectron in its three-dimensional framework was projected onto this The Abel Inverse Basis Set Expansion (BASEX) transformation method was applied to the initial three-dimensional distribution, and photoelectron spectra were acquired by reorganizing the corresponding three-dimensional images. The experimental results were corrected through the Au − anion, 33 and the recorded energy resolution from the current instrument was more than 5%.…”
mentioning
confidence: 99%